2022
DOI: 10.1093/milmed/usac029
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypocalcemia With Mortality of Combat Casualties With Brain Injury and Polytrauma Transported by Critical Care Air Transport Teams

Abstract: Introduction Hypocalcemia at hospital presentation is associated with increased mortality in trauma patients with hemorrhagic shock. The 2019 updates to the Joint Trauma System Damage Control Resuscitation (DCR) Clinical Practice Guideline recommend calcium supplementation for ionized calcium (iCa) measurements <1.2 mmol/L. Ionized calcium goals for en route critical care (ERCC) following DCR are less defined, and the impact of in-flight hypocalcemia events among critically injured com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In some studies, hypocalcemia is a strong independent predictor of mortality [4,8,9], but in other studies, the association of hypocalcemia with mortality is found only in univariate analysis, and after adjusting for other clinical parameters, this association has disappeared [6]. Other studies found no association between hypocalcemia and mortality in hospitalized patients with COVID-19 or other diseases [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…In some studies, hypocalcemia is a strong independent predictor of mortality [4,8,9], but in other studies, the association of hypocalcemia with mortality is found only in univariate analysis, and after adjusting for other clinical parameters, this association has disappeared [6]. Other studies found no association between hypocalcemia and mortality in hospitalized patients with COVID-19 or other diseases [10][11][12].…”
Section: Introductionmentioning
confidence: 98%